Praktik Sosial Remaja Penyalahguna Narkoba - Muhammad Fakhri Aziz; Hayana Muslimah; Yuanita Dwi Hapsari; Gunawan Gunawan (Riviera Publishing, 2025)
The involvement of adolescents in drug abuse has led to a disruption of the social system, with a significant increase in the last 5 years. It was recorded that 1.44% of adolescents were involved in drugs in 2021, increasing to 1.52% in 2023. This behavior is assumed by the growth of self-awareness involvement supported by structures that facilitate it, while acknowledging the existence of forms of barriers, including social norms and legal restrictions on deviant activities related to drug abuse. Using a qualitative approach based on Anthony Giddens' structuring theory, it seeks to describe drug abuse practices in identifying supporting factors (enabling), inhibiting (constraining), and aspects of adolescent agency in adolescent drug abuse practices. This research produced an illustration, namely there are six enabling structures: low attention from parents, friends, environment, intelligence, unsatisfactory work, and life principles. Two constraining structures were found, namely the police and police spies, as well as the family. The agency factor is in the form of the meaning of practice as an activity to work and the schemata of the usefulness of drugs.